Latinx shakespeares : staging U.S. intracultural theater - Della Gatta, Carla (University of Michigan Press, 2023)
Latinx peoples and culture have permeated Shakespearean performance in the United States for over 75 years--a phenomenon that, until now, has been largely overlooked as Shakespeare studies has taken a global turn in recent years. Author Carla Della Gatta argues that theater-makers and historians must acknowledge this presence and influence in order to truly engage the complexity of American Shakespeares. Latinx Shakespeares investigates the history, dramaturgy, and language of the more than 140 Latinx-themed Shakespearean productions in the United States since the 1960s--the era of West Side Story. This first-ever book of Latinx representation in the most-performed playwright's canon offers a new methodology for reading ethnic theater looks beyond the visual to prioritize aural signifiers such as music, accents, and the Spanish language. The book's focus is on textual adaptations or performances in which Shakespearean plays, stories, or characters are made Latinx through stage techniques, aesthetics, processes for art-making (including casting), and modes of storytelling. The case studies range from performances at large repertory theaters to small community theaters and from established directors to emerging playwrights. To analyze these productions, the book draws on interviews with practitioners, script analysis, first-hand practitioner insight, and interdisciplinary theoretical lenses, largely by scholars of color. Latinx Shakespeares moves toward healing by reclaiming Shakespeare as a borrower, adapter, and creator of language whose oeuvre has too often been mobilized in the service of a culturally specific English-language whiteness that cannot extricate itself from its origins within the establishment of European/British colonialism/imperialism.